A frameless picture frame test with embedded sensor: Mitigation of imperfections in shear characterization of woven fabrics. (1st March 2019) - Montazerian, H.; Rashidi, A.; Hoorfar, M.; Milani, A.S.
Abstract: Picture frame test (PFT) is frequently employed for characterizing the shear behavior of woven fabrics. In the present study, the main sources of possible imperfections in the PFT, arising from the operator error during sample installation, to the fixture misalignment and the inherent non-uniformities within the fabric, are reviewed and modeled using the kinematic as well as continuum-based approaches. Upon new understandings from these models, a new test methodology was designed where the shearing frame boundary condition is inscribed on the fabric sample itself during sample preparation; in lieu of fabricating and installing a metallic picture frame. The new frameless picture frame (FPF) test was proven to effectively mitigate the imperfections and provide a simple operation and better control and uniformity of the fabric installation and deformation. Contrary to the conventional PFT, the wrinkling behavior and normalized force response in the FPF was in agreement with the conventional bias extension test, with no close-to-arm fiber bending, while showing a superior test repeatability at both loading and unloading stages. Finally, a mechanically compatible, stretchable sensor was developed and integrated into the fabric samples to monitor and verify the induced local deformation along the yarns under different test methods.